INTERNATIONAL CONFERENCE ON APPLICATIONS OF VIRTUAL REALITY IN PERFORMING ARTS AND THE BALLETWHERE PROJECT - BÓLYA, ANNA MÁRIA (Macedón Tudományos és Kulturális Közlemények, 2023)
Absztrakt A cikk a „3Dance 3Didactics” nagyprojekt részét képező “Balletwhere – Testing a ballet historical 3D classroom as an educational, collaborative and promotional space” keretében zajló konferenciáról ad ismertetést. A „Conference on Applications of Virtual Reality in Performing Arts” címmel megrendezett esemény 2022 augusztusában zajlott, az Ohridi-tó partján. Abstract The article reports on the conference that was held in the frame of project "Balletwhere - Testing a ballet historical 3D classroom as an educational, collaborative and promotional space", which is part of the "3Dance 3Didactics" larger project. The event, entitled "Conference on Applications of Virtual Reality in Performing Arts", took place in August 2022 on the shores of Lake Ohrid.